Student’s digital literacy:: gamification as a strategy for teaching and learning in classes in the first years of Ifac’s integrated high school - Gomes Amorim, Risonete; Ferreira, Edilene da Silva (The ESPecialist, 2024)
The present research aims to investigate how the use of digital technologies, through the lens of gamification, can favor the teaching/learning of the Portuguese language in the first-year high school classes of the Computer Networks course at the Institute of Education, Science and Technology of Acre – Ifac, from the perspective of the teachers. The goal is to understand the importance of using these active methodologies in the classroom, as well as the contribution of these actions to the digital literacy of students. In this sense, considering the globalized era we are in, this research is relevant when we propose to work with digital technology that brings about significant changes for the social, intellectual, and professional development of individuals in all sectors of society. To support this research, the following theoretical framework was used: Alves (2015), Kleiman (2007), Leffa (2014), Rojo (2012), Soares (2002), among others. The methodology adopted is bibliographical, has a qualitative-quantitative nature, and it was also carried out through field research with Ifac teachers. Questionnaires with open and closed-ended questions were used as instruments to generate data. The results indicate that the use of gamification, although still modest, can contribute to the digital literacy of students.